2010
DOI: 10.1007/s11334-009-0111-6
|View full text |Cite
|
Sign up to set email alerts
|

An agile approach to language modelling and development

Abstract: We have developed novel techniques for component-based specification of programming languages. In our approach, the semantics of each fundamental programming construct is specified independently, using an inherently modular framework such that no reformulation is needed when constructs are combined. A language specification consists of an unrestricted context-free grammar for the syntax of programs, together with an analysis of each language construct in terms of fundamental constructs. An open-ended collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, having to deal with both BAS and action notation was a drawback. Mosses et al [25,43,45,46] reported on subsequent work that led to the present paper.…”
Section: Related Workmentioning
confidence: 60%
“…However, having to deal with both BAS and action notation was a drawback. Mosses et al [25,43,45,46] reported on subsequent work that led to the present paper.…”
Section: Related Workmentioning
confidence: 60%
“…Funcons of PLanCompS [13] are composable components for PL mechanisation each of which with a universally unique semantics. Funcons are similar to our syntax components except that, due to our decoupling of syntax and semantics, our components can have multiple pieces of semantics.…”
Section: Related Workmentioning
confidence: 99%